(untitled) (International Journal of Ayurveda and Pharma Research, 2018)
Agni in Ayurveda has a significant role to maintain body homeostasis, body functioning, metabolism of body and proper functioning of body. Agni in Ayurveda is correlated with digestive power of the body. There are many reasons behind the maintenance of Agni (digestive power of body) in Ayurveda. The main reason behind its maintenance is that it helps in growth and development of the body. Agni is basically divided in three types which have further types and the main three types which maintain body balance are Jhataragni (digestive fire), Bhutagni and Dhatuvagni (metabolism at cellular level). They work together to maintain the balance in the body as Jhataragni is maintaining metabolism and Bhutagni and Dhatuagni is maintaining the cellular metabolism. Imbalance in the physiology of Agni is the main cause for the formation of Ama which is the main reason for many diseases. So Agni is important for every function of body. This article shows the importance of Agni and significance of Agni in Ayurveda.